Estimation of the IDGREY model and by adaptive interaction applied to an EMG30 dc motor (LACCEI, 2024)
This research carried out the development of the experimental model through the acquisition of data from a direct current motor, through the identification of a gray box model for speed control under the LabVIEW platform. The precision of the experimental model was validated by solving the speed control problem of the DC motor, in this case the adaptive interaction control technique was applied to a multilayer perceptron network, obtaining as a result an error prediction of 97%. With which it is concluded that the system adapts quite well to the precision of the model.